Effect of sowing time and different levels of nitrogen on yield and quality of barley (Hordeum vulgare L.) - Sandhu, Kanwaljit; Singh, Manpreet; Singh, Harjinder; Kumar, Dinesh; Kumar, Parveen (Annals of Agricultural Research, 2017)
The field experiment was conducted during 2013-14 and 2014-15 at Students' Research Farm, KhalsaCollege, Amritsar to study the effect of time of sowing on yield and quality of barley (Hordeumvulgare L.) under different levels of nitrogen. The experiment was laid out in split-plot design withthree replications. Three dates of sowing (20 October, 5 November and 20 November) were kept inmain-plots and four levels of nitrogen (control, 50, 62.5 and 75 kg N/ha) were kept in sub-plots.Crop sown on 20 November recorded higher yield attributing characters (number of effectivetillers, number of grains per ear and 1000- grain weight) grain and malt yield during both the years.Among nitrogen levels 62.5 kg N/ha gave maximum yield attributing characters (number of effectivetillers, number of grains per ear and 1000- grain weight) grain and malt yield during 2013-14 and2014-15. However, malt recovery was highest in 20 October sowing and control than all othertreatments during both years.